Implementation of a parallel XTS encryption mode of operation - Alomari, Mohammad Ahmed; Samsudin, Khairulmizam; Ramli, Abdul Rahman (Indian Society for Education and Environment, 2014)
Security of data stored inside storage devices is becoming one of the main issues in computer security now. It is known that the most efficient techniques to protect storage devices are using cryptography. Developing newer and more secure encryption algorithms and modes of operation might be critically important to protect these devices since conventional disk encryption algorithms, such as CBC mode, have shown serious security flaws. In this paper, the IEEE XTS encryption mode of operation for storage encryption (P1619 standard) has been implemented using parallel design. A performance comparison between the sequential and parallel algorithms of XTS mode is presented here. Parallel overheads that prevented from achieving perfect linear speedup are measured and minimized. The parallel XTS algorithm has shown a speedup of 1.80, with 90% efficiency, faster than the sequential algorithm. In these simulations, AES is used as encryption algorithm with 256-bit encryption key.